Molecular characterization of Euptychiina (Lepidoptera: Satyrinae) from the northern Central Cordillera of the Andes - MARÍN, MARIO ALEJANDRO; LÓPEZ, ANDRÉS; LUCCI-FREITAS, ANDRÉ VICTOR; URIBE, SANDRA INÉS (Revista Colombiana de Entomología, 2009)
Euptychiina is considered a taxonomically difficult group given a high diversity of species and morphological homogeneity among them, making their identification complex. In this sense, DNA sequences offer a useful tool for species differentiation, providing valuable and complementary information to traditional morphological characters. The molecular characterization of thirteen Euptychiina species common to the northern Central Cordillera of the Colombian Andes was carried out using mitochondrial DNA sequences of the 3’ Cyt b gene, the tRNASer and the terminal portion of 3’ ND1. Sequences of the DNA fragments exhibited a degree of variation adequate for differentiating all species. Nucleotide variation was less than 2% at the intraspecific level and greater than 4% at the interspecific level. Additionally, an intergenic spacer was found in the Cyt b and the tRNASer  that has not previously been reported for the Nymphalidae. Nucleotide variation in the spacer at the interspecific level was similar and complementary to that found in the coding region. The sequenced fragment is presented as a new tool to improve and complement taxonomic studies in groups like this, which include morphologically similar species. The proposed region combines various genes with different degrees of nucleotide variation, providing useful information for species identification.